In-service teacher training: Analysis of the Andalusian legislation - Hijano Trujillo, Azahara (Avances en Supervisión Educativa, 2021)
This article analyzes the backbones of Andalusian policy regarding in-service training for non-university teachers. For this, the contrast between the academic bibliography on the subject and the most relevant legislation approved by the Government of Andalusia is used, mainly in the last five years. The result of this reflection supposes a positive assessment of what has been done up to now, both due to the link between the academic literature on this subject and the aforementioned regulations, as well as the issues promoted by the Administration. Conclusions that we consider significant for the approval of the future IV Permanent Teacher Training Plan.
Keywords: education policy; teacher training; in-service teacher training; teaching profession